Orientation rotation behavior in aluminum alloys during dissimilar channel angular pressing - Han, JH; Suh, JY; Oh, KH; Lee, JC (JAPAN INST METALS, 2004)
The crystallographic orientation rotation behaviors in aluminum alloys during dissimilar channel angular pressing (DCAP) were investigated. Experiments were conducted to observe the texture evolution due to DCAP. Texture simulation using the full constraint Taylor calculations based on the rate sensitivity model was also carried out both to explain the experimental results and to elucidate the rotation behaviors of the individual orientations due to DCAP.
Keywords: CONFINED STRIP SHEARING; EQUAL-CHANNEL; TEXTURE EVOLUTION; MICROSTRUCTURE; EXTRUSION; SHEET